Comparative transcriptomic provides novel insights into the soybean response to Colletotrichum truncatum infection - Boufleur, Thaís R.; Massola Júnior, Nelson S.; Becerra, Sioly; Baraldi, Elena; Bibiano, Líllian B. J.; Sukno, Serenella A.; Thon, Michael R.; Baroncelli, Riccardo (Frontiers in Plant Science, 2022)
Soybean (Glycine max) is among the most important crops in the world and its production can be threatened by biotic diseases, such as anthracnose. Soybean anthracnose is a seed-borne disease mainly caused by the hemibiotrophic fungus Colletotrichum truncatum. Typical symptoms are pre- and post-emergence damping-off, necrotic lesions on cotyledons, petioles, leaves, and pods. Anthracnose symptoms can appear early in the field, causing major losses to soybean production. In preliminary experiments, we observed that the same soybean cultivar can have a range of susceptibility towards different strains of C. truncatum, while the same C. truncatum strain can cause varying levels of disease severity in different soybean cultivars. To gain a better understanding of the molecular mechanisms regulating the early response of different soybean cultivars to different C. truncatum strains, we performed pathogenicity assays to select two soybean cultivars with significantly different susceptibility to two different C. truncatum strains and analyzed their transcriptome profiles at different time-points of interaction (0, 12, 48, and 120 hours post-inoculation - hpi). The pathogenicity assays showed that the soybean cultivar Gm1 is more resistant to C. truncatum strain 1080, and it is highly susceptible to strain 1059, while cultivar Gm2 shows the opposite behavior. However, if only trivial anthracnose symptoms appeared in the More Resistant Phenotype (MRP; Gm1-1080; Gm2-1059) upon 120 hpi, in the More Susceptible Phenotype (MSP; Gm-1059; Gm2- 1080) plants show mild symptoms already at 72 hpi, after which disease evolved rapidly to severe necrosis and plant death. Interestingly, several genes related to different cellular responses of the plant immune system (pathogen recognition, signaling events, transcriptional reprogramming, and defense-related genes) were commonly modulated at the same time-points only in both MRP. The list of differentially expressed genes (DEGs) specific to the more resistant combinations and related to different cellular responses of the plant immune system may shed light on the important host defense pathways against soybean anthracnose.